Figures de l’exil dans New Grub Street de George Gissing - Christine Huguet (Cahiers Victoriens et Edouardiens)
The sense of exclusion is ubiquitous in George Gissing’s fiction ; whether it be heavily foregrounded from the title page, most notably in Born in Exile, or merely suggested by the intrinsic reality inseparably bound up with it. In New Grub Street, Gissing’s acknowledged masterpiece combining autobiographical resonances with an insider’s dissection of the contemporary literary scene, estrangement is raised to the level of systematised exile, it is monopolised and articulated as a logical predicate.This paper will look at Gissing’s comprehensive vertical exploration of the concepts of belonging and exclusion in this 1891 novel which, being deeply rooted in material and metaphysical uprooting, tremulously urges the paradox of exile at home.